Understory vegetation diversity, soil properties and microbial community response to different thinning intensities in Cryptomeria japonica var. sinensis plantations - Liu, Kai-Li; Chen, Bo-Yao; Zhang, Bin; Wang, Rui-Hui; Wang, Chun-Sheng (Frontiers in Microbiology, 2023)
Soil microorganisms are the key factors in elucidating the effects of thinning on tree growth performance, but the effects of vegetation and soil on the species composition and function of soil microorganisms after thinning are still not well elaborated. The effects of thinning on understory vegetation diversity, soil physicochemical properties and soil microbial community composition were investigated in a thinning trial plantation of Cryptomeria japonica var. sinensis, including four thinning intensities (control: 0%, LIT: 20%, MIT: 30% and HIT: 40%), and the relationships of the microbial community structure with the understory vegetation diversity and soil properties were assessed. The results showed that thinning had a greater effect on the diversity of the shrub layer than the herb layer. The soil bulk density and the contents of soil organic matter, total potassium and nitrogen increased with increasing thinning intensities. The Shannon and Chao indices of soil bacteria and fungi were significantly lower in the LIT, MIT and HIT treatments than in the control. Thinning can significantly increase the abundance of Proteobacteria and Actinobacteria, and higher thinning intensities led to a higher relative abundance of Ascomycota and a lower relative abundance of Basidiomycota, Rozellomycota and Mortierellomycota. Redundancy analysis indicated that soil physicochemical properties rather than understory vegetation diversity were the main drivers of microbial communities, and fungi were more sensitive to soil properties than bacteria. Functional prediction showed that thinning significantly reduced the potential risk of human diseases and plant pathogens, and the nitrogen fixation capacity of bacteria was the highest in the HIT treatment. Thinning significantly increased the relative abundance of cellulolysis and soil saprotrophs in bacteria and fungi. The findings provide important insights into the effects of thinning on C. japonica var. sinensis plantation ecosystems, which is essential for developing thinning strategies to promote their ecological and economic benefits.